Integrasi Hukum Islam Di Kerajaan Demak Abad XVI M: Telaah Terhadap Serat Angger Suryo Alam - M Irfan Riyadi; Khairil Umami (Ascarya: Journal of Islamic Science, Culture, and Social Studies, 2021)
: The transfer of government from Majapahit to Demak at the end of the 15th century, as well as a transition from the Hindu era to the Islamic era, also gave birth to social, political, cultural, and legal transformations. The pattern of the penetration of Islam into peaceful Javanese culture, or penetration pacifique, has shown integration in all fields. Integration creates a stable and equilibrium condition. The question that then arises is how Demak produces laws that are able to create such stable conditions. It is important to do this on the fiber Suryangalam legal text of the Demak era. The purpose of this study is to identify the Serat Suryo Alam manuscript, explore Islamic law legislation in the text, and explain how the Islamic kingdom of Demak carried out social engineering to realize a just and peaceful society. Then to answer the problem, philological and historical methods are used, while the analysis uses content analysis with Talcott Parson's integration theory. This study concludes that: 1) the Suryo Alam manuscript is a legal text that can be found in the digitization of British Library manuscripts, 2) this manuscript contains legal, material, and judicial sources at the same time, and 3) social engineering can be measured by the stages of adaptation of Hindu and Islamic law, with the Trirasa Goal of efforts, legal integration, and efforts to maintain the law in people's social lives or latency. This stage gave birth to an equilibrium society of tata titi tentrem gemahripah loh jinawi kartaraharja.